PENGARUH MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN TERHADAP HIGHER ORDER THINKING SKILLS SISWA PADA KELAS IV SEKOLAH DASAR - Anita Ika Inayah; Agustiningsih; Arik Aguk Wardoyo (Universitas Negeri Surabaya, 2022)
Abstract This study aims to determine the effect of predict observe explain learning model on the higher order thiking skills of elementary school students. The type of research used in this study is experimental research. The study was conducted in the fourth grade of SDN 2 Tampo, with the subject of research 45 students. The method of data collection was conducted by interviews and tests of high thinking ability. Data analysis techniques using SPSS application version 21 to determine the normality test and t-test Test. The results of normality test analysis obtained the significance value of class IVA is 0.346 while Class IVB is 0.123, it can be concluded that the normality test data has been normally distributed. Based on the T-test results are calculated with the help of SPSS software shows the value of t-calculted > t-table (2.766>1.683). Thus the value obtained from the results of t-calculated and t- table show that Ha is accepted and H0 is rejected. So it can be concluded that there is an influence of predict observe explain learning model on the higher order thiking skills of elementary school students. Keywords: experiment Research, predict observe explain